A rogue at Stonecliffe - Camp, Candace (Camp, Candace. Stonecliffe novel., 2023)
When the love of her life left without any explanation, Annabeth Winfield moved on despairingly, knowing she'd never have a love as thrilling as her first ever again. Sloane Rutherford was roguish and daring, but as Annabeth grew up, she realized that their reckless romance was just a passing adventure, never meant for stability. Twelve years later, Annabeth is engaged to someone new, ready to start her life with a dependable man. That's when Sloane returns. And he brings with him a serious warning: Annabeth is in trouble. After spending the past dozen years working as a spy, Sloane thought he'd left espionage behind him. But now a dangerous blackmailer is after Annabeth. Sloane offers to hide his former lover at Stonecliffe, the Rutherford estate, but stubborn Annabeth demands to be part of the investigation. As the two embark on a dangerous and exciting journey, memories of their past romance resurface. Sloane and Annabeth aren't the wide-eyed children they used to be, but knowing they're wrong for each other makes a nostalgic affair seem very right...